Semantic Polonicisms in the Russian Chancery Language of the First Half of the 17th Century - Павловна Гарбyль, Людмила (Slavistica Vilnensis, 2002)
The article examines the history of the following words found in diplomatic correspondence from Muscovite Russia (first half of 17th cen.): beg in the meaning ‘rotation of the heavenly bodies’, vzajem in the meaning ‘mutually, reciprocally’, voznik in the meaning ‘draught-horse, carriage-horse’, dostaviti in the meaning ‘to convey; to bring’, dochožen ’e in the meaning ‘attainment, achievement’, žaloba in the meaning ‘mourning’ and životnyj in the meaning ‘abdominal’.